The Outflowing [O ii] Nebulae of Compact Starburst Galaxies at z ∼ 0.5 - Serena Perrotta; Alison L. Coil; David S. N. Rupke; Wenmeng Ning; Brendan Duong; Aleksandar M. Diamond-Stanic; Drummond B. Fielding; James E. Geach; Ryan C. Hickox; John Moustakas; Gregory H. Rudnick; Paul H. Sell; et al. (The Astrophysical Journal, 2024)
High-velocity outflows are ubiquitous in compact, massive ( M _* ∼ 10 ^11 M _⊙ ), z ∼ 0.5 galaxies with extreme star formation surface densities (Σ _SFR ∼ 2000 M _⊙ yr ^−1 kpc ^−2 ). We have previously detected and characterized these outflows using Mg ii absorption lines. To probe their full extent, we present Keck/KCWI integral field spectroscopy of the [O ii ] and Mg ii emission nebulae surrounding all of the 12 galaxies in this study. We find that [O ii ] is more effective than Mg ii in tracing low surface brightness, extended emission in these galaxies. The [O ii ] nebulae are spatially extended beyond the stars, with radial extent R _90 between 10 and 40 kpc. The nebulae exhibit nongravitational motions, indicating galactic outflows with maximum blueshifted velocities ranging from −335 to −1920 km s ^−1 . The outflow kinematics correlate with the bursty star formation histories of these galaxies. Galaxies with the most recent bursts of star formation (within the last <3 Myr) exhibit the highest central velocity dispersions ( σ ≳ 400 km s ^−1 ), while the oldest bursts have the lowest-velocity outflows. Many galaxies exhibit both high-velocity cores and more extended, slower-moving gas indicative of multiple outflow episodes. The slower, larger outflows occurred earlier and have decelerated as they propagate into the circumgalactic medium and mix on timescales ≳50 Myr.